3D TDOA/AOA Localization in MIMO Passive Radar with Transmitter and Receiver Position Errors. (15th March 2022) - Huang, Donghua; Zhao, Yongsheng; Hu, Dexiu; Zhao, Yongjun
Abstract : This paper deals with the problem of determining the position of a single target from time difference of arrival (TDOA) and angle of arrival (AOA) measurements using multitransmitter multireceiver passive radar system with widely separated antennas. A practically motivating scenario where the transmitter and receiver positions are contaminated by errors is addressed. First, the reduction in localization accuracy due to the presence of transmitter and receiver position errors is derived through the Cramér-Rao lower bound (CRLB) analysis. Then, a novel algebraic localization algorithm based on weighted least squares minimization is proposed that takes the transmitter and receiver position errors into consideration to reduce the estimation error. The proposed solution is shown theoretically to reach the CRLB even when the transmitter and receiver positions have errors. Simulation results also verify the theoretical developments and the performance improvement of the proposed solution over existing algorithms.